ISLAMIC HUMAN RESOURCE MANAGEMENT AND MAQASHID SYARIAH: A SYSTEMATIC LITERATURE REVIEW - Nurma Yulita (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2025)
The development of Islamic human resource management (IHRM) increasingly emphasizes ethical, humanistic, and sustainable approaches in response to the limitations of conventional human resource management, which often prioritizes efficiency and financial performance while neglecting human welfare. In the context of a Muslim majority, Islamic values (especially maqashid al-shariah) offer a comprehensive normative framework that promotes justice, human dignity, and holistic well-being. This study aims to conduct a systematic review and synthesis of existing literature on human resource management through the perspective of maqashid shariah, identifying key themes, conceptual frameworks, and research gaps. Using a qualitative Systematic Literature Review (SLR) approach, relevant studies published in accessible national and international journals were collected through databases such as Google Scholar and DOAJ. The selected literature was analyzed using content and thematic analysis to identify dominant patterns and trends. Findings indicate that Sharia-based human resource management contributes to an ethical work culture, employee well-being, fair compensation, sustainable human capital development, and organizational sustainability. However, most existing studies are still conceptual or context-specific, with limited empirical validation and unstandardized measurement models. This study concludes that sharia maqasid provides a strong conceptual foundation for developing human resource management, while future research should focus on operationalizing indicators, developing empirical models, and testing them in various organizational contexts.